2012
DOI: 10.1016/j.febslet.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory changes in adipose tissue enhance expression of GPR84, a medium‐chain fatty acid receptor

Abstract: a b s t r a c tIn this study we aimed to identify the physiological roles of G protein-coupled receptor 84 (GPR84) in adipose tissue, together with medium-chain fatty acids (MCFAs), the specific ligands for GPR84. In mice, high-fat diet up-regulated GPR84 expression in fat pads. In 3T3-L1 adipocytes, co-culture with a macrophage cell line, RAW264, or TNFa remarkably enhanced GPR84 expression. In the presence of TNFa, MCFAs down-regulated adiponectin mRNA expression in 3T3-L1 adipocytes. Taken together, our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 21 publications
7
75
0
Order By: Relevance
“…Neutrophils are also observed to be infiltrated in adipose tissue and may have a role in the initiating event(s) of the inflammatory cascade (40). Nagasaki et al (41) recently reported that high fat diet-fed mice up-regulated GPR84 expression in adipose tissue. TNF␣-treated 3T3-L1 adipocytes remarkably enhanced GPR84 expression, and MCFAs down-regulated adiponectin mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are also observed to be infiltrated in adipose tissue and may have a role in the initiating event(s) of the inflammatory cascade (40). Nagasaki et al (41) recently reported that high fat diet-fed mice up-regulated GPR84 expression in adipose tissue. TNF␣-treated 3T3-L1 adipocytes remarkably enhanced GPR84 expression, and MCFAs down-regulated adiponectin mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Its ligands are medium-chain free fatty acids (FFAs), and it functions obviously as a lipid/ FFA sensor (35). It was suggested that GPR84 acts as a proinflammatory receptor linking fatty acid metabolism to immunological res ponses (34)(35)(36). Other fatty acids such as arachidonic acid and saturated fatty acids have been demonstrated to increase proinflammatory IL-8 along with numerous other inflammatory factors, including IL-6, TNF-α, IL-1β and CXCL1 (37).…”
Section: Factor Analysis Identified Cinc1-3 Mip-1/3` Mig Rantes Anmentioning
confidence: 99%
“…In animal models of endotoxemia and multiple sclerosis (experimental autoimmune encephalomyelitis), GPR84 is upregulated in microglia, suggesting that GPR84 may regulate the processes of neural inflammation (Bouchard et al, 2007). GPR84 has also been shown to emerge in adipocytes in response to tumor necrosis factor a secreted by the infiltrating macrophages, and activation of this receptor by MCFAs enhances the inhibitory effect of tumor necrosis factor a on adiponectin expression in adipocytes, suggesting that GPR84 may exacerbate obesity-associated insulin resistance (Nagasaki et al, 2012). It has also been demonstrated that GPR84 in zebrafish is involved in the accumulation of intracellular lipid droplets, and undecanoic acid can enhance LPS-induced IL-12 p40 production through GPR84 in zebrafish, indicating that GPR84 is a direct factor bridging fatty acid metabolism and immunologic regulation (Huang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%